Multiple endoscopic biopsy sites to increase detection of Helicobacter pylori infection - Ahmad Junaidi bin Ahmad Hamidi (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Helicobacter pylori infection affects almost half of the population and remains clinically significant in the development of chronic gastritis and increased risk of gastric malignancy. However, its prevalence is found to be low in Pahang population where the practice of single antral biopsy during endoscopy has been advocated. Our aim for this research is to determine the role of multiple biopsy sites during OGDS to increase the detection of Helicobacter pylori infection. The Updated Sydney System recommended five biopsy sites for biopsy which includes antrum, incisura angularis and body of stomach. This is a cross sectional study of 141 patients with clinical diagnosis of gastritis or dyspepsia who underwent OGDS in endoscopy suite HTAA, Kuantan and HoSHAS, Temerloh from January 2016 to December 2016. Five biopsy sites have been obtained and tested with CLOtest and send for histology. The positive result for Helicobacter pylori infection by CLOtest and/ or histology together with sociodemographic data, endoscopic diagnosis and histology characteristics were recorded and analysed using IBM SPSS Statistic version 23. A total of 17 patients were diagnosed with Helicobacter pylori infection, making the prevalence of the infection to 12%. No significant difference seen in most of the parameters studied. However, we found out that single antral biopsy can missed the infection rate up to 35%. In conclusion, multiple biopsy sites during endoscopy can increase detection of Helicobacter pylori infection.